(untitled) (Research, Society and Development, 2023)
Increasingly, people are looking for treatments to improve the appearance of their skin, prioritizing effective, quick-to-apply and affordable options. Collagen bio-stimulators are known for their ability to increase skin firmness, elasticity, and support, making them a popular choice. The objective of this study is to evaluate the effects of these products on the skin with a focus on reducing aging. Scientific articles, dissertations, monographs, and these were considered. The databases used were Brasil Scientific Electronic Library Online (SciELO), Medical Literature Analysis and Retrieval System Online (MedLine) and Google Scholar. The results highlighted collagen’s ability to reach the deepest layers of the skin, promoting firmness and hydration, meeting the expectations of those looking for these treatments. Different collagen-based products have shown effectiveness in reversing intrinsic and extrinsic aging but emphasizing the need for an evaluation by an experienced and qualified professional. Despite several benefits, it was possible to observe the importance of mentioning that these products can generate adverse effects, which may be immediate, medium, or long term, and it is important to reinforce the need for clear communication with the patient. The pharmacist began to be recognized for his work in aesthetic health, in addition to being able to assume technical responsibility for a health establishment. However, it is important to emphasize that all pharmaceutical activity must be based on compliance with the regulatory standards that govern the profession to guarantee safety to users regarding the applicable procedures and the effectiveness of the therapeutic resources used.